Hospital Chaplaincy in the Twenty-first Century : the Crisis of Spiritual Care on the NHS - Swift, Christopher, 1965- (Explorations in practical, pastoral, and empirical theology., 2014)
This book charts the changing role of hospital chaplains and examines through detailed case studies the realities of practice and the political debates which either threaten or sustain the service. This second edition includes a new introduction and updated material throughout to present fresh insights and research about chaplaincy, including in relation to New Atheism and the developing debate about secularism and religion in public life.